Moderate regular physical exercise can help in alleviating the systemic impact of schistosomiasis infection on brain cognitive function - Berkiks, Inssaf; Abdel Aziz, Nada; Moses, Blessing; Brombacher, Tiroyaone; Brombacher, Frank (Frontiers in Immunology, 2025)
One of the major consequences of schistosomiasis is its impact on brain function, and despite its severity, the underlying mechanism(s) remain inadequately understood, highlighting a knowledge gap in the disease. The symptoms can vary from headaches to profound cognitive impairment. Besides, the potential influence of physical exercise in mitigating cognitive deficits has received little attention. In our study, we utilized a murine model of Schistosoma mansoni infection to investigate the cognitive impact of schistosomiasis. Our aims were multifaceted: to pinpoint the specific cognitive domains affected during the infection in adult mice, to unravel the complex interplay between glial and immune cells within the central nervous system (CNS), and crucially, to explore the potential therapeutic role of regular physical exercise in counteracting the deleterious effects of schistosomiasis on the CNS. Our findings unveiled that while acute infection did not disrupt simple and complex learning or spatial reference memory, it did induce significant deficits in recall memory—a critical aspect of cognitive function. Furthermore, our investigation unearthed profound alterations in the immune and glial cell populations within the CNS. Notably, we observed marked changes in CD4+ T cells and eosinophils in the meninges, as well as alterations in glial cell dynamics within the hippocampus and other brain regions. These alterations were characterized by heightened microglial activation, diminished astrocyte reactivity and a shift towards a proinflammatory milieu within the CNS. We also provided insights into the transformative potential of regular moderate physical exercise in partially alleviating cognitive and neuroinflammatory consequences of schistosomiasis. Remarkably, exercise decreased glial cell production of TNFα, suggesting a shift towards a less pro-inflammatory environment. Collectively, our study provided compelling evidence of the intricate interplay between schistosomiasis infection and cognitive function, underscoring the critical need for further exploration in this area. Furthermore, our findings demonstrated the positive effects of physical activities on mitigating the cognitive burden of schistosomiasis, offering new hope for patients afflicted by this debilitating disease.